Design of the observation queue scheduler for WEAVE on the WHT - Farina, C; Dominguez-Palmero, L; Benn, C; Guest, S; Morris, H; Pico, S; Carlos Abrams, D; Aguerri, JAL; Bonifacio, P; Carrasco, E; Dalton, G; Middleton, K; et al. (Society of Photo-Optical Instrumentation Engineers, 2018)
The Observation Queue Scheduler (OQS) for WEAVE is described in this paper, with particular emphasis on the scheduling algorithm. WEAVE is the new 2-deg field of view multi-object (1000 multiplex) spectroscopy facility (R5000 and R20000) at the 4.2-m William Herschel Telescope. The OQS helps to maximize the scientific impact of WEAVE observations by optimising the schedule of the observing blocks, taking into account the science priority, required instrument configuration and observing constraints. On a nightly basis the OQS will assist the observer in creating a flexible queue of suitable observing blocks to be executed. It will be also possible to run a version of the OQS for extended periods of time to provide guidance on the longer-term planning of WEAVE surveys.